Religious factors affecting death anxiety in older adults practicing Hinduism. Issue 8 (14th September 2022) - Lamba, Nishtha; Bhatia, Aditi; Shrivastava, Anita; Raghavan, Archana
Abstract: The aim of the study was to examine the influence of religion on death anxiety in older adults ( N = 105) practicing Hinduism and visiting the Kumbh pilgrimage. Standardized questionnaires and brief interviews were administered in participants' native language. Pilgrims with higher religiosity had lower death anxiety compared to pilgrims with lower religiosity. Greater belief in the cycle of rebirth, an increased presence of meaning in life, and less continued search of meaning in life were significantly associated with lower death anxiety. The findings provide support for incorporating religious and spiritual awareness for older adults in community health settings.